Expenditures on Mental Health Care in the Czech Republic in 2015 - Broulikova, Hana M; Dlouhy, Martin; Winkler, Petr (The Psychiatric quarterly, 2020)
Expenditures on mental health care in the Czech Republic are not being published regularly, yet they are indispensable for evaluation of the ongoing reform of Czech mental health care. The main objective of this study is to estimate the size of these expenditures in 2015 and make a comparison with the last available figures from the year 2006. The estimation is based on an OECD methodology of health accounts, which structures health care expenditures according to health care functions, provider industries, and payers. The expenditures are further decomposed according to diagnoses, and inputs used in service production. The amount spent on mental health care in 2015 reached more than 13.7 billion Czech korunas (EUR 501.6 million), which represented 4.08% of the total health care expenditures. This ratio is almost identical with the 2006 share (4.14%). There are no significant changes in the relative expenditures on mental health care and in the structure of service provision. The Czech mental health care system remains largely hospital based with most of all mental health care expenditures being spent on inpatient care. Future developments in the expenditures will indicate the success of the current effort to deinstitutionalise mental health care.
Keywords: Deinstitutionalization; Česká republika; hospitalizace; Czech Republic; Health Expenditures; Central and Eastern Europe; Mental health care reform; Expenditures on psychiatric care; lidé; OECD system of health accounts; výdaje na zdravotnictví; Mental Health Services; Humans; služby péče o duševní zdraví; Mental Disorders; duševní poruchy; Hospitalization